THE EFFECT OF MIND MAPPING WITH PICTURE WORD CARDS TOWARD THE ABILITY OF EARLY READING FOR A HARD OF HEARING STUDENT - Nurika Miftakul Janah; Saichudin . (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
A Student with hard of hearing hasa limited vocabulary and difficulty understanding abstract words. The purposes of this research were to describe: (1) the ability of early reading for a hard of hearing student at the time before the intervention, (2) the ability of early reading for a hard of hearing student after the intervention, and (3) the effect of mind mapping with picture word card toward the ability of early reading for a hard of hearing student in the class I. This study used a single subject research (SSR) with A-B-A design. These results indicated that there was a positive effect of the mind mapping with picture word card toward the ability of early reading for a hard of hearing student in the class I.